Model Matematika Efek Perpindahan Polutan Pada Kolam Pertama Ke Kolam Kedua Dipengaruhi Adveksi Dan Dispersi - Alya Anzira; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2020)
Abstract —Pollution in the aquaculture environment can come from inedible food and not eaten by fish. In a variety of fish culture business basin become the choice for entrepreneurs, fish entrepreneurs have many basins for fish farming.Concentration of pollutans in the basin will decrease when the first basin is entering clean water, so pollutants will come out of the basin. Based on the results of research into the mathematical model of water pollution in the form of a partial differential equation system.Keywords — Mathematical Model, Water Pollution, n Basin.